2018
DOI: 10.1093/jac/dky286
|View full text |Cite
|
Sign up to set email alerts
|

European guidelines for primary antifungal prophylaxis in adult haematology patients: summary of the updated recommendations from the European Conference on Infections in Leukaemia

Abstract: The European Conference on Infections in Leukaemia (ECIL) updated its guidelines on antifungal prophylaxis for adults using the grading system of IDSA. The guidelines were extended to provide recommendations for other haematological diseases besides AML and recipients of an allogeneic haematopoietic stem cell transplantation (HSCT). Posaconazole remains the drug of choice when the incidence of invasive mould diseases exceeds 8%. For patients undergoing remission-induction chemotherapy for AML and myelodysplast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
226
0
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(244 citation statements)
references
References 56 publications
6
226
0
12
Order By: Relevance
“…Our patient developed a disseminated Aspergillus flavus infection with multiple subcutaneous, muscular and parenchymal lesions. IA is an unexpected finding in paediatric ALL at the beginning of the first line therapy, as we observed in our patient: no antifungal prophylaxis is usually recommended in paediatric ALL [18][19][20]. Even if patient's personal history was positive for a traumatic event, disseminated IA was more likely the consequence of fungal vascular migration from an initial pulmonary site than direct inoculation of Aspergillus flavus into the skin, also considering that no cutaneous laceration was detected or referred.…”
Section: Discussionmentioning
confidence: 52%
“…Our patient developed a disseminated Aspergillus flavus infection with multiple subcutaneous, muscular and parenchymal lesions. IA is an unexpected finding in paediatric ALL at the beginning of the first line therapy, as we observed in our patient: no antifungal prophylaxis is usually recommended in paediatric ALL [18][19][20]. Even if patient's personal history was positive for a traumatic event, disseminated IA was more likely the consequence of fungal vascular migration from an initial pulmonary site than direct inoculation of Aspergillus flavus into the skin, also considering that no cutaneous laceration was detected or referred.…”
Section: Discussionmentioning
confidence: 52%
“…Invasive fungal infections (IFIs) remain a leading cause of morbidity and mortality in patients with haematologic diseases . Antifungal prophylaxis has already been proven to be clinically effective in preventing IFIs in high‐risk patients with haematologic diseases, and primary antifungal prophylaxis (PAP), particularly mould‐active azole in high‐risk groups is now a standard protocol in international guidelines . These recent advances in the use of PAP during chemotherapy and haematopoietic stem cell transplantation (HSCT) have reduced the number of IFIs and improved the survival of high‐risk patients .…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiology studies have demonstrated that mold infections (e.g., Aspergillus species) are more prevalent in neutropenic hematologic malignancy populations . Prophylactic use of antifungals with a broader spectrum of activity, such as voriconazole, reduce the incidence of invasive fungal disease, although breakthrough infections are commonly observed …”
mentioning
confidence: 99%
“…Voriconazole is an effective antifungal prophylactic and is recommended as primary treatment for invasive aspergillosis in immunocompromised patients . Voriconazole displays highly variable nonlinear pharmacokinetics, and there is a strong correlation between voriconazole plasma trough concentrations and clinical outcomes in those with invasive fungal infections .…”
mentioning
confidence: 99%